Role of Business Technologies in the Outperformance of Firms - Mahesh Chandra Joshi; Gaurav Gupta; Deepak Bansal (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
Since the onset of Industrial Revolution in Europe and United States, Technology becameintegral part of production and business. Started in 1712 the pace of research and innovation has becomemultifold. Started with technologies like Spinning Jenny, Newcomen steam engine, Locomotive,Telegraph communications, Photograph, Printing Machines the progressive journey includedtechnologies and products like Electricity, Automobile, phonograph, Airplane, Antibiotics, AtomicPower, Insecticides, Computers, Internet, Cloud, Robots, Artificial intelligence, Big Data and manymore to count. Technologies have significant influence on the business and society. According toeconomic historian Paul Bairoch (1750) Third World (Asia, Africa, Latin America) had GNP (PPP) inbillions of US dollars* 495 while First World (Western Europe, Northern America, Japan, Singapore andSouth Korea) had GNP (PPP) in billions of US dollars 155. In the year 1990, it reached to GNP (PPP) inbillions of US dollars 7640 and 19210 respectively. Empirical studies show that apart fromLiberalization, Privatization and Globalization (LPG), technological advances have influenced businessthroughout the world and lead to mass production, mass marketing and automation. On one hand it hashelped many firms including Indian to outperform on financial fronts but created challenges and threatsfor small firms. It has also resulted in to ethical and environmental concerns especially for ThirdWorld.Those Indian firms who relies on technologies have high market value like Reliance Jio ($65Billion/2020), Honda Cars India Ltd. (HCIL) , Grofers ($1 Billion), Paytm ($16 Billion), Flipkart ($37.6Billion). These companies have explored opportunities with the help of Emerging Technologies andmany are close to financial outperformance.